Prediction of Pavement Life Using Influence Function and Peak Influence Function for Mechanistic-Empirical Pavement Design Analysis - Buhari, Rosnawati (International Journal of Integrated Engineering, 2020)
The aim of this study is to predict the long-term pavement life using different method of analysis of the primary response in the pavement layer. The methods are influence function method (IFM) and Peak Influence Function Method (PIFM). A tyre-pavement interaction model was used to predict the 3-Dimensional contact stresses under static and dynamic loads. In this model, a truck tyre was loaded on a three-layer flexible pavement surface. The load primarily affects the vertical contact stress and the longitudinal contact stress. Statistical method was used to analyse the compare the differences between both methods. As a result, elastic modulus of the asphaltic material varies with asphaltic concrete thickness, vehicle speed, volume of void, volume of bitumen and temperature. Temperature was found to influence the asphaltic material modulus more than others due to the elastic modulus of the mixture’s dependency on the stiffness of the bitumen. It is succeeded by vehicle speed, volume of void, volume of binder and AC thickness of which is minimal or have almost no effect on strains. In conclusion, Peak influence function is able to predict the response in pavement as a result of vehicle loads sufficiently and realistically. Low differences of strain was evidenced to reduce the differences resulting in failure.